The Aesthetics of Seeing in Seamus Heaney’s Seeing Things: Memory and Transcendence-in-Immanence in the Aesthetics of Everyday Life - Moreira, Jéssica (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
The aim of this paper is to deconstruct not only the things that Seamus Heaney sees in his collection of poems Seeing Things but, more importantly, how those things are perceived. In order to do so, I will be applying Husserl’s phenomenological concept of transcendence-in-immanence and different philosophical theories of perception, such as adverbial theory, to construct a useful device with which to read and look at what Seamus Heaney is seeing. In Seeing Things, unlike in previous collections, the perceptual experience of objects and these objects themselves will be transubstantiated and, therefore, transcended. The things perceived acquire a double status: they are both “there,” in the tangible world to be observed, but also “beyond,” in an ethereal realm in which they are “made different.” These theories push us, however, even deeper into the rabbit hole: into the problem of the ontological and the phenomenological status of the object and the problem of representation. These issues will be examined according to Heaney’s own process of signifying them, for example: childhood memory, the death of his father and notions of limits and boundaries (which relate to concepts of binarism such as presence and absence). Furthermore, memory is the medium through which the ordinary and the visionary overlap and become transparent, but also the domain in which ontological meaning is restored after the revelation of the paradoxes that memory itself produces: for it is in memory that contraries intermingle – contraries such as life and death, fullness and emptiness, presence and absence.